MiRNAs from serum-derived extracellular vesicles as biomarkers for uveal melanoma progression - Wróblewska, Joanna Patrycja; Lach, Michał Stefan; Rucinski, Marcin; Piotrowski, Igor; Galus, Lukasz; Suchorska, Wiktoria Maria; Kreis, Stephanie; Marszałek, Andrzej (Frontiers in Cell and Developmental Biology, 2022)
Uveal melanoma (UM) is a rare type of malignancy that originates from melanocytes located in the choroid, iris and the ciliary body of the eye. UM has a very high mortality upon metastatic spread to the liver, the prime target organ for UM metastasis. The lack of effective therapies for advanced stages of the disease aggravate the prognosis further. Moreover, biomarkers for early detection and progression of UM, especially the molecular traits governing the development of metastasis, are still not available in clinical practice. One extensively studied components of liquid biopsies are exosomes, a subtype of extracellular vesicle. Due to their unique molecular cargo, they could be used as carriers of early markers of cancer development and progression. For characterisation of the miRNA profiles present in circulating serum-derived exosomes of patients with diagnosed primary and metastatic UM, we have analysed the miRNA cargos using next-generation sequencing followed by RT-qPCR validation in a cohort of patients (control n=20; primary n=9; metastatic n=11). Nine miRNAs clearly differentiating these patient groups have been established. We show that hsa-miR-223 and hsa-miR-203a are the most promising biomarker candidates, allowing categorization of patients into local and advanced UM. Additionally, the comparison of miRNA expression levels in exosomes derived from UM patients with those derived from healthy donors, revealed that hsa-miR-144 has the potential to be used as an early marker for presence of UM. Taken together, this pilot study reveals that miRNAs extracted from circulating exosomes could be exploited as potential biomarkers in UM diagnosis and, more importantly, for indicating metastatic spread.